Comparison of three nickel-based carbon composite catalysts for hydrogen evolution reaction in alkaline solution. (7th September 2017) - Wang, Lixin; Li, Yao; Yin, Xucai; Wang, Yazhou; Lu, Lin; Song, Ailing; Xia, Meirong; Li, Zhiping; Qin, Xiujuan; Shao, Guangjie
Abstract: In this work, preparing three nickel-based carbon composite catalysts (Ni-OCNT, Ni-ONC and Ni-rGO) by supergravity field electrodeposition for hydrogen evolution reaction (HER) from nickel sulfamate bath containing suspended nano-sized carbon materials. The crystal structure, morphology and chemical compositions of the composite catalysts were characterized by XRD and SEM measurements. The electrochemical activity of composite coatings for HER was determined by polarization measurement and electrochemical impedance spectroscopy in 1.0 M NaOH solution. The prepared nickel-based carbon composite catalysts exhibit a significant enhancement in electrocatalytic activity for HER compared with pure Ni electrode. In addition, the Ni-rGO, Ni-ONC, Ni-OCNT catalysts prepared under supergravity field demand overpotentials of 245, 177, 91 mV and 286, 224, 154 mV and 330, 286, 222 mV to drive current densities of 80, 30, 10 mA cm −2, respectively. Ni-rGO cathode presents excellent HER activity with lowest overpotentials. Highlights: The Ni-based carbon composite catalysts show superior stability under large current density. The crystal plane of Ni (111) plays an important role in enhancing the electrochemical activity. Ni particles grow on carbon materials more uniformly under supergravity electrodeposition. Graphene exhibits more specific surface than CNT and biomass carbon.